Comparison of Ultrasonography Features and K-TIRADS for Isthmic and Lobar Papillary Thyroid Carcinomas: A Single-Center Study - Lee, Yoo Jin; Kim, Dong Wook; Shin, Gi Won; Park, Jin Young; Choo, Hye Jung; Park, Ha Kyoung; Ha, Tae Kwun; Kim, Do Hun; Jung, Soo Jin; Park, Ji Sun; Moon, Sung Ho; Ahn, Ki Jung; et al. (Frontiers in Endocrinology, 2020)
Objective: This study aimed to compare ultrasonography (US) features and the Korean-Thyroid Imaging Reporting and Data System (K-TIRADS) categories for diagnosing isthmic and lobar papillary thyroid carcinomas (PTC). Methods: From January 2009 to December 2012, 163 patients who underwent thyroid surgery and were confirmed with a postoperative histopathological diagnosis of isthmic PTC were retrospectively included. Fifty-nine patients were excluded because their tumor size was < 0.5 cm or because of other reasons. The control group comprised of 145 patients who underwent thyroid surgery from January to April 2013 for a classic type of PTC, with the largest diameter being ≥ 0.5 cm and located in the thyroid lobe. A single radiologist retrospectively reviewed the US features and K-TIRADS categories of each nodule using a picture archiving and communication system. Results: Among 104 patients with isthmic PTC, 95 and 9 had primary and secondary cancers, respectively. On the other hand, all 145 patients with lobar PTC had primary cancers. Isthmic PTC showed a lower prevalence of non-parallel orientation than lobar PTC (23.1% and 71%). Nodule orientation was the only US feature statistically different between the two groups (p < 0.0001). However, there was no significant difference in patient age, sex, nodule size, composition, echogenicity, microcalcification, spiculated/microlobulated margin, and K-TIRADS category between the two groups (p > 0.05). Conclusions: K-TIRADS may be useful in the diagnosis of both isthmic and lobar PTC.